Recent advances in DNA walker machines and their applications coupled with signal amplification strategies: A critical review - Xu, Mingdi; Tang, Dianping (Analytica chimica acta, 2021)
DNA walkers, a type of dynamic nanomachines, have become the subject of burgeoning research in the field of biology. These walkers are powered by driving forces based on strand displacement reactions, protein enzyme/DNAzyme reactions and conformational transitions. With the unique properties of high directionality, flexibility and efficiency, DNA walkers move progressively and autonomously along multiple dimensional tracks, offering abundant and promising applications in biosensing, material assembly and synthesis, and early cancer diagnosis. Notably, DNA walkers identified as signal amplifiers can be combined with various amplification approaches to enhance signal transduction and amplify biosensor sensing signals. Herein, we systematically and comprehensively review the walking principles of various DNA walkers and the recent progress on multiple dimensional tracks by presenting representative examples and an insightful discussion. We also summarized and categorized the diverse signal amplification strategies with which DNA walkers have coupled. Finally, we outline the challenges and future trends of DNA walker machines in emerging analytical fields. [Display omitted] •We critically review recent advances in DNA walkers for bioanalytical application.•Different DNA walkers based on three characteristic driving forces are discussed.•DNA walkers based on multiple dimensional tracks are assessed for amplified sensing signal.•DNA walkers coupled with diverse signal amplification strategies are sorted and evaluated.